Are Self-regarding Subjects More Strategic? - Benito Arru\~nada; Marco Casari; Francesca Pancotto (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
To investigate the relationship between the depth of strategic thinking and social preferences we ask subjects in an experiment to perform dictator games and a guessing game. The guessing game measures depth of strategic thinking while dictator games control for social preferences. When performing a comparison within the same degree of strategic reasoning, self-regarding subjects show more strategic sophistication than other subjects.
Keywords: C91; C92; D63; 330